An Isolation Amplifier-Based Front-End Circuit for Grounded Capacitive Sensors - Gelmini, Daniel (2024)
A novel front-end circuit for capacitive sensors with one terminal grounded is proposed and evaluated in this article. For the first time, it is suggested to employ an isolation amplifier (IsoAmp) in the front-end circuit of a capacitive sensor. Thanks to this IsoAmp, a floating voltage source is generated that appropriately excites the capacitive sensor. In addition, the concept of active shielding is applied so as to be able to measure remote sensors that are interconnected through a shielded cable. The theoretical, simulation, and experimental results reported herein demonstrate that the sensitivity of the circuit does not depend on the parasitic capacitance of the cable. However, such a parasitic does alter the offset of the input-output characteristic mainly due to the non-idealities of the IsoAmp. In terms of linearity, the proposed front-end circuit offers remarkable values, with a maximum non-linearity error of around 0.1% Full-Scale Span (FSS) in the 1-10 pF range, and 0.01% FSS in the 10-100 pF range.